Moral Ideology, the Ideal Child, and the Hidden Adult in Let’s Read Children’s Stories: A Nodelmanian Reading of Mukena Mita and Sayang Anak Yatim - Indriyani, Jiphie Gilia; Adzhani, Shabrina An; Savitri, Ima Dyah; Murnieatie, Itznaniyah Umie (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study examines the representation of moral ideology, the construction of the ideal child, and the influence of adult perspectives in two Indonesian children’s stories, Mukena Mita and Sayang Anak Yatim. The research applies the theoretical framework proposed by Perry Nodelman, particularly the concepts of ideology, the ideal child, and the hidden adult within the field of Children's Literature Studies. Using a qualitative textual analysis approach, the study analyzes narrative structures, character development, and selected textual excerpts to identify how moral values are constructed and communicated in the stories. The findings reveal that both narratives strongly emphasize moral ideology related to empathy, generosity, and social responsibility. Mukena Mita represents moral development through a process of personal reflection in which the protagonist learns to prioritize empathy over personal desire. In contrast, Sayang Anak Yatim portrays moral awareness through direct exposure to social realities, encouraging children to express compassion toward vulnerable individuals. The study also demonstrates that both stories construct an image of the ideal child characterized by kindness, humility, and concern for others. Furthermore, the analysis highlights the role of the “hidden adult,” in which adult perspectives guide the narrative and validate moral interpretations. Although distributed through the digital platform Let's Read, the stories continue to reflect traditional ideological functions of children’s literature by transmitting adult moral expectations to young readers.